THE QUR’ANIC PERSPECTIVE ON ECOLOGY IN ṬABĀRĪ AND ṬABĀṬABĀ’Ī INTERPRETATION - Febriani, Nur Arfiyah; Aziz Waktar, Alfi Sachdeva; Tamam, Badru (Mumtaz: Jurnal Studi Al-Quran dan Keislaman, 2020)
The Intergovernmental Panel on Climate Change (IPCC) at the end of 2019 launched findings on global warming which increased by 0.5%. The lifestyle of modern humans starting from the anthropocentric paradigm is often said to be a trigger for environmental damage. Interestingly, anthropocentric precisely argued the teachings of celestial religion which became the basis of his thought. This paper aims to make a reconciliation effort towards the anthropocentric paradigm by providing an explanation of the views of the Koran which are read through the thoughts of Ṭabārī and Ṭabāṭabā'ī related to the pattern of human and natural interaction. Using the maudu'i interpretation method and based on scientific arguments through Ecology studies, this paper discovers Ṭabārī and Ṭabāṭabā'ī's views on ecological concepts that can be understood in the sense of: "The study of the interactions between nature and humans in the ecosystem where they grow and develop and benefit each other with the same goal, namely to worship God ". This is based on findings about the spiritual dimension between nature and humans in the activities and purposes of creation revealed by the Koran. With this view, humans can use natural resources while preserving them as a khalīfah fī al-Arḍ/natural conservator, as Allah's mandate to humans in the Koran.